2015
DOI: 10.1039/c4ee03515a
|View full text |Cite
|
Sign up to set email alerts
|

The materials genome in action: identifying the performance limits for methane storage

Abstract: Analogous to the way the Human Genome Project advanced an array of biological sciences by mapping the human genome, the Materials Genome Initiative aims to enhance our understanding of the fundamentals of materials science by providing the information we need to accelerate the development of new materials.This approach is particularly applicable to recently developed classes of nanoporous materials, such as metal-organic frameworks (MOFs), which are synthesized from a limited set of molecular building blocks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
382
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(415 citation statements)
references
References 58 publications
(122 reference statements)
7
382
0
1
Order By: Relevance
“…For example, it was found that a region of high performing materials possessed largest cavity diameters of 10 -12 Å 31,36 , a region which was later expanded to 8.0 -14.5 Å when a wider breadth of materials was considered 30 . Likewise, several studies…”
Section: H2 Methane Storagementioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was found that a region of high performing materials possessed largest cavity diameters of 10 -12 Å 31,36 , a region which was later expanded to 8.0 -14.5 Å when a wider breadth of materials was considered 30 . Likewise, several studies…”
Section: H2 Methane Storagementioning
confidence: 99%
“…Methane storage capacity is by far the most studied sorption property in the field of computational high throughput screening of nanoporous materials [27][28][29][30][31][32][33][34][35][36][37]83 . There are several reasons for this, the first being that there is considerable interest in safely and efficiently storing methane for use as an alternative, clean-burning fuel in motor vehicles.…”
Section: H2 Methane Storagementioning
confidence: 99%
See 1 more Smart Citation
“…These data are accessible through the production MP website via a porous materials "app" [11] that allows for interactive browsing of the multidimensional space of porous materials properties. This graphical search interface allows the user to plot the values of pairs of properties, pan and zoom on the graph, and then list all materials in a region of interest, and select from that list for a detailed per-material view.…”
Section: Nanoporous Materials Explorermentioning
confidence: 99%
“…The absorption and dynamics of H 2 and CH 4 among other light gases (CO, CO 2 , N 2 …) when confined to the internal cages of mesoporous structures has received great interest in recent years because of the potential use of these mesoporous materials (MOFs, MCM, zeolites...) for the storage and transport of commercially important gases [1][2][3][4][5][6][7]. The efficiencies of various nanoporous and microporous materials for storage and ease of removal depend crucially on the thermodynamic properties of these gases at or near the surfaces of the chosen materials [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%